Antioxidative Defense System, Hormones, and Metabolite Accumulation in Different Plant Parts of Two Contrasting Rice Cultivars as Influenced by Plant Growth Regulators Under Heat Stress - Al-Zahrani, Hassan S.; Alharby, Hesham F.; Fahad, Shah (Frontiers in Plant Science, 2022)
We examined the metabolic, hormonal, enzymatic, and non-enzymatic responses of various plant components (leaf, root, and xylem sap) to plant growth regulators [methyl jasmonate (MeJA), ascorbic acid (Vc), brassinosteroids (Br), triazoles (Tr), alpha-tocopherol (Ve), and control] under heat stress [ambient temperature (AT), heat stress at night time (HNT), and heat stress at day (HDT)] in heat-sensitive (IR-64) and heat-tolerant (Huanghuazhan) rice cultivars under greenhouse conditions. Our results showed that heat stress altered the antioxidant activities and hormonal balance and rigorously reduced total soluble sugars, proteins, and proline, whereas increases were observed in H2O2 and Malondialdehyde (MDA) content accumulation in the plant xylem sap and leaves of both tested cultivars; however, the impact was more pronounced in IR-64. The superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX), glutathione reductase (GR), Glutathione (GSH), dehydroascorbate reductase (DHAR), and monodehydroascorbate reductase (MDHAR) activities were higher in Huanghuazhan than in IR-64 in response to temperature stress, when compared to AT. Additionally, heat stress increased abscisic acid (ABA) levels in both rice cultivars, especially in IR-64. The highest concentrations of hormones were recorded in the roots, followed by the leaves and xylem sap, in both cultivars. HDT and HNT stresses severely reduced the concentrations of all of the cytokinin types (except for iP9G and tZ9G) and IAA in the different plant parts of rice cultivars. Moreover, HNT was more detrimental for hormone and metabolite synthesis in both cultivars. The growth regulators (especially Vc + Br + Ve + MeJA) were comparatively more effective in minimizing the hostile impact of heat stress on most of the studied traits and should be applied to obtain the optimum yield of rice in subtropical and tropical areas under changing climatic conditions.